Atomically dispersed Ni activates adjacent Ce sites for enhanced electrocatalytic oxygen evolution activity - Pei, Zhihao (2023)
Manipulating the intrinsic activity of heterogeneous catalysts at the atomic level is an effective strategy to improve the electrocatalytic performances but remains challenging. Here, atomically dispersed Ni anchored on CeO2 particles entrenched on peanut-shaped hollow nitrogen-doped carbon structures (a-Ni/CeO2@NC) is rationally designed and synthesized. The as-prepared a-Ni/CeO2@NC catalyst exhibits substantially boosted intrinsic activity and greatly reduced overpotential for the electrocatalytic oxygen evolution reaction. Experimental and theoretical results demonstrate that the decoration of isolated Ni species over the CeO2 induces electronic coupling and redistribution, thus resulting in the activation of the adjacent Ce sites around Ni atoms and greatly accelerated oxygen evolution kinetics. This work provides a promising strategy to explore the electronic regulation and intrinsic activity improvement at the atomic level, thereby improving the electrocatalytic activity.